T93. RESHAPING THE DIAGNOSTIC BORDERS OF SCHIZOPHRENIA: THE LOOK OF HISTORY OF PSYCHIATRIC PRACTICES. (18th May 2020) - Clauss, Julie; Danion-Grilliat, Anne; Scarfone, Marianna; Hess, Volker; Bonah, Christian
Abstract: Background: The diagnostic concept of Schizophrenia as defined by DSM and ICD is increasingly being questioned. It is criticized above all for its lack of validity. It refers to very heterogeneous disorders in terms of signs and symptoms but also in terms of evolution and heritability. Clinicians and researchers are therefore considering how to rethink this concept, in the absence of known physiopathological mechanisms and etiology, by integrating various advances in fields such as genetics, molecular biology, brain imaging and cognitive sciences. However, the renewal of the concept of schizophrenia has yet to be explored in terms of its potential impact on psychiatric practice. It is an essential point because this diagnostic concept does not correspond to a theoretical entity that exists for itself but it is a tool of psychiatrists' daily practice when they seek to name the disorders presented by a patient. Thus, a renewal of the concept of schizophrenia would necessarily have an impact on the diagnoses made by psychiatrists and we know how important the diagnosis in psychiatry is: for the medical care but also for the personal history of the patient. This impact that a renewal of the concept of schizophrenia could have on the diagnostic practices of psychiatrists can be better understood through the analysis of a historical example: the introduction of the concept of Schizophrenia at the Psychiatric Clinic of Strasbourg in France during the period 1920–1930. The concept of Schizophrenia was first discussed in 1908 by the swiss psychiatrist Eugen Bleuler at the Annual Meeting of the German Psychiatric Association in Berlin. At the Psychiatric Clinic of Strasbourg, it was first used by psychiatrists in 1922. How did this then new concept find its place among the other diagnostic concepts that had been used until then in this institution? Methods: In an attempt to answer this question, we implemented a methodology that combined a quantitative and a qualitative approach. The first is a retrospective descriptive statistical study whose objective is to establish the evolution of the proportion of the different diagnoses made at the Psychiatric Clinic of Strasbourg during the period 1920–1930. This study includes all hospitalized patients and uses admission records for data collection. This quantitative approach was complemented by a qualitative approach that consists in reconstructing the diagnostic trajectory of some patients with a diagnosis of schizophrenia after the period of introduction of this concept. The diagnoses made during their previous hospitalizations were systematically collected and analyzed, this time using the medical records of these patients as sources. Results: The diagnostic concept of Schizophrenia seems to have replaced the one of Dementia praecox within the diagnostic practices: the latter was given extensively in 1924, but hardly any longer in 1928. However, in the same period of time, other diagnostic concepts of the field of psychosis like Manic-depressive Illness were less commonly used while others like Catatonia were increasingly employed. The reconstruction of patients' diagnostic trajectories tends to show that the diagnostic of schizophrenia would have taken over from the diagnostic of Dementia Praecox but also from some of the diagnoses of Manic-depressive Illness, Hebephrenia and Psychopathy. Discussion: This historical perspective makes it possible to understand the impact on psychiatrist's diagnostic practices of a "nosological innovation" that is theoretical, such as the renewal of the concept of schizophrenia could be. In the diagnostic practices, one diagnostic concept would not simply replace another, but it's introduction could induce a broader reshaping of diagnostic mapping.